Strategi Komunikasi Petani Dalam Difusi Inovasi Padi Organik - selly Oktarina; Thirtawati . (Metacommunication, 2018)
Organic farming is an agricultural system that is designed and managed in such a wayso as tocreate sustainable productivity. Agricultural extensionagents is one of there formers who havean important role in the diffusion of innovation activities of organic rice program. The success of education is not only determined by the material presentedal one but delivery technique also plays an important roleinthe success ofagricultural extensionactivities. Therefore, itis necessary that the communication strategy of an innovationcan bediffusedto farmers. With the effective communication strategy will facilitate the extensionin presenting the materialin various ways according to theapproach taken.This research was conducted in the Village Pulokerto Palembang. Points were selected intentionally (purposive) to farmers who perform semi-organic rice cultivation. When the study conducted from May to November 2014. The method includes a case study (case study) of selected farmers, farmers selected from farmers who take the whole organic rice cultivation (census) as respondentsBased on the research results can be summarized as follows: (1). SO strategyisa strategy that uses the power(strenghts) totake advantage of opportunities that exist.; (2).  WO strategy is astrategy adoptedby minimizing weaknesses (weaknesses) to take advantage of opportunitiesthatare owned; (3). ST strategy is a strategy that is performed with the way of using force(strengths) to address threats; (4).  WT strategy is astrategy used by minimizing the weaknesses and avoiding all thethreats(threats) Key words: communication strategies, diffusion of innovation, organic farming